Targeted Yield Based Integrated Nutrient Management of Egg plant in Torripsamment (Indian Journal of Arid Horticulture, 2014)
Soil test crop response correlation studies were conducted to formulate the fertilizer adjustment equations for egg  plant (Var. Kanhaya F hybrid) under integrated plant nutrition system in Torripsamment during kharif 2010 following 1 Ramamoorthy's inductive-cum-targeted yield approach. The nutrient requirement for producing one quintal fruit yield of  egg plant was 0.31, 0.05 and 1.31 kg of N, P O and K O, respectively. The per cent contribution from soil and fertilizer 2 5 2 nutrients were found to be 44.98 and 13.57 for nitrogen, 23.75 and 3.06 for phosphorus and 21.97 and 26.68 for potassium,  respectively. The per cent organic nutrient contribution of FYM was 29.14 for nitrogen, 10.06 for phosphorus and 30.28 for  -1 potassium. As per the IPNS based fertilizer prescription equation, for obtaining 250 q ha fruit yield of egg plant on an  -1 Torripsammant considering the average soil test values of 110, 40 and 25 kg ha of available N, P and K, respectively the  requirement of fertilizer nutrients will be 98.4, 31.6 and 59.1 kg ha of N, P2O5 and K2O, respectively along with 15 t FYM ha
Keywords: Egg plant; STCR-IPNS; fertilizer adjustment equation; Torripsamment